Електронно-мікроскопічне дослідження слизової оболонки фундального відділу шлунка під час дії меланіну на тлі хронічної гіпергастринемії - Вороніна, Олена; Дзержинський, Микола; Берегова, Тетяна; Voronina, Olena; Dzerzhinsky, Mykola; Beregova, Tetyana (Східноєвропейський національний університет імені Лесі Українки, 2016)
Проведено ультраструктурне дослідження слизової оболонки фундального відділу шлунка щурів за тривалої гіпергастринемії та під час дії пігменту меланіну. Показано, що при гіпергастринемії в усіх шарах слизової оболонки шлунка відбуваються зміни, які свідчать про ії малігнізацію. Уведення меланіну нівелює трофічну дію надлишкового гастрину на епітеліоцити слизової оболонкишлунка щурів. Using electron microscopy, ultrastructural changes in fundus mucosa of rats suffering from hypergastrinemia following melanin treatment were investigated. Studies were conducted using 30 male rats. Selected areas of stomach fundus were analyzed in rats which received: 28 days of single omeprazole injections, 28 days of combined omeprazole and melanin injections, and соntrol animals. Hypergastrinemia induced ultrastructural changes were observed in all mucosal layers, indicating clear malignization. Atypic epithelial cells, destruction of their protein-synthesizing apparatus, lack of endocrine cells differentiation were found. Introduction of melanin was shown to eliminate the trophic effect of excessive gastrin levels to the epithelial cells of gastric mucosa in rats, as evidenced by the appearance of differentiated endocrine cells, restoration of secretory function of epithelial cells and lack of atypical cells.
Ultrastructural Effects in Fundus Mucosa of Rats with Hypergastrinemia under the Influence of Exogenous Melanin.
Keywords: гіпергастринемія; меланін; малігнізація; слизова оболонка шлунка; hypergastrinemia; melanin; malignization; fundus mucosa of stomach